Phantom orbit : a thriller [large type] - Ignatius, David, 1950- (Thorndike Press large print high octane., 2024)
avid Ignatius is known for his uncanny ability, in novel after novel, to predict the next great national security headline. In Phantom Orbit, he presents a story both searing and topical, with stakes as far-reaching as outer space. It follows Ivan Volkov, a Russian student in Beijing, who discovers an unsolved puzzle in the writings of the seventeenth-century astronomer Johannes Kepler. He takes the puzzle to a senior scientist in the Chinese space program and declares his intention to solve it. Volkov returns to Moscow and continues his secret work. The puzzle holds untold consequences for space warfare. The years pass, and they are not kind to Volkov. After the loss of his son, a prosecutor who'd been too tough on corruption, and Russia's invasion of Ukraine, Volkov makes the fraught decision to contact the CIA. He writes: Satellites are your enemies, especially your own. . . . Hidden codes can make time stop and turn north into south. . . . If you are smart, you will find me.